2020
DOI: 10.1186/s13075-020-02198-9
|View full text |Cite
|
Sign up to set email alerts
|

Circulating TNF-like protein 1A (TL1A) is elevated early in rheumatoid arthritis and depends on TNF

Abstract: Background: The tumor necrosis factor (TNF) superfamily cytokine TNF-like protein 1A (TL1A) and its receptor DR3 are essential for diverse animal models of autoimmune disease and may be pathogenic in rheumatoid arthritis (RA). However, the relationship of TL1A to disease duration, activity, and response to anti-TNF and other therapies in RA is not clear. Methods: We measured soluble TL1A in synovial fluid (SF), serum, or plasma from RA first-degree relatives (FDRs) and in early RA and established disease. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Therefore, a positive feedback loop is present between the two cytokines. Previous study results in the RA patient serum have revealed the inhibition of TL1A production via anti-TNF-a ( 28 ). The results of the present study supports these findings, in which the inhalation of TNF-a induce TL1A/DR3 expression in mice, and the reduction of TL1A/DR3 in asthmatic mice is induced by OVA after anti-TNF-a treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, a positive feedback loop is present between the two cytokines. Previous study results in the RA patient serum have revealed the inhibition of TL1A production via anti-TNF-a ( 28 ). The results of the present study supports these findings, in which the inhalation of TNF-a induce TL1A/DR3 expression in mice, and the reduction of TL1A/DR3 in asthmatic mice is induced by OVA after anti-TNF-a treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Activation of the TNFRSF25 signaling pathway by its cognate ligand, tumor necrosis factor‐like cytokine 1A (TL1A), which is mainly expressed by antigen‐presenting and endothelial cells, 21 promotes cytokine production 22 . These interactions serve as co‐stimulatory signals and have been linked to exacerbations of inflammatory diseases such as asthma, rheumatoid arthritis, inflammatory bowel disease, and skin psoriasis 23–27 . Additionally, agonistic stimulation of TNFRSF25 leads to antigen‐specific T cell proliferation, a feature that has been explored in the areas of vaccinology, 28 infectious diseases, 29 and oncology 30 …”
Section: Discussionmentioning
confidence: 99%
“…22 These interactions serve as co-stimulatory signals and have been linked to exacerbations of inflammatory diseases such as asthma, rheumatoid arthritis, inflammatory bowel disease, and skin psoriasis. [23][24][25][26][27] Additionally, agonistic stimulation of TNFRSF25 leads to antigen-specific T cell proliferation, a feature that has been explored in the areas of vaccinology, 28 infectious diseases, 29 and oncology. 30 True to its co-stimulatory role, TNFRSF25 signaling, beyond the need for TL1A, requires T-cell receptor (TCR) engagement by cognate antigens and the presence of IL-2.…”
Section: Discussionmentioning
confidence: 99%
“…CIA is a model of human RA with similar histopathological and clinical features ( 62 ). After treatment with anti-TL1A antibody, total joint score was decreased and clinical inflammation of CIA mice was effectively alleviated, which was mediated by blocking the TL1A/DR3 signaling pathways ( 63 ). Similarly, compared to WT mice, TL1A gene knockout mice had improved clinical profiles for CIA (improved synovial hyperplasia and cartilage erosion) through reduction of inflammatory cells infiltration and reduced production of pathogenic antigens ( 58 ).…”
Section: Association Between Tl1a and Inflammatory Autoimmune Diseasesmentioning
confidence: 99%
“…TL1A levels in serum and synovial fluid were higher in RA patients when compared to that in healthy controls and correlated with expression of rheumatoid factor (RF), anti-cyclic citrullinated peptide (anti-CCP), as well as disease activity ( Table 1 ) ( 63 , 68 , 69 ). RF and anti-CCP antibodies are promising disease markers for early diagnosis and prognosis of RA ( 63 ).…”
Section: Association Between Tl1a and Inflammatory Autoimmune Diseasesmentioning
confidence: 99%